Computational prediction of soot formation rates for combustion of plastics - Novozhilov, V. (2008)
Plastic materials enjoy significant share of overall combustible loads in modern buildings. The purpose of the present project is to develop a practical model of soot formation resulting from combustion of plastic materials burning during compartment fires. The ability to predict soot production rates of these materials will contribute significantly to development of fire-safe design methods for modern buildings.